للتنبؤ بتعثر المصارف (Estrella et al , 2000) اختبار القدرة التنبؤية للنموذج اللوجيستي - الفرجاني إبراهيم مسعود (Scientific Journal of University of Benghazi, 2020)
The aim of the research is to test the predictive ability of the logistic model of (Estrella et al, 2000) To predict the default of banks in order to reveal the financial difficulties and problems that may lead to the default of banks. To achieve this, the research relied on the logistical model of (Estrella et al, 2000) It was applied to the financial sample data from the commercial banks of Libyan during the period 2009-2014. The results of the analysis showed the accuracy of the model (Esterella et al, 2000In the classification of banks included in the research sample, reaching 100% during the entire research period. The research recommended a set of recommendations, the most important of which are: The adoption by the supervisory authorities of Libyan banks commercial of the model (Esterella et al, 2000He alsorecommended the necessity to oblige Libyan commercial banks to disclose all important and necessary financial information that could help in developing and applying many models that may have great importance in determining the status of these banks in the future.